Stress Test the financial health of the Vietnam commercial bank during the Covid-19 pandemic - Nguyen Quoc Anh; Tang My Sang (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2022)
The Covid-19 pandemic has had an impact on many aspects of the economy, including commercial banking. The effect of the pandemic on the bank’s operation through three main channels, when the pandemic happens, many enterprises have to stop production and business, individuals and households face many difficulties, the change in consumer behavior and investment structure of enterprises or foreign investors. The financial situation of these subjects affects the operation of the bank. The study aims to understand the impact of the pandemic on the financial health of banks in the early stages of the pandemic. Secondary data for the period 2017 to 2020 was collected from the financial statements of 24 Vietnamese commercial banks. The indicators are analyzed using a paired t-test. The article has identified three issues to be concerned about during the pandemic: (1) The liquidity index increases; (2) Non-performing loans decreased while under normal conditions, this index increases continuously over the years; (3) Return on asset increases while under normal conditions, this index decreases continuously over the years. Then, the article proposes implications for solutions to help banks operate efficiently during the pandemic. This study offers a new understanding of the effect of the pandemic on banking operations in Vietnam, a country whose financial system depends mainly on banks.